Response Growth And Yield Of Sweet Corn Cultivated On Peat Soil As Influence Of Coffee Skin Ash And Cow Manure Application - Dina Lestari; Setia Budi; Siti Hadijah (Jurnal Sains Pertanian Equator, 2020)
The research is aimed to determine the effect of ash and cow manure on growth and yield of sweet corn cultivated on peat soil. Ash applied in this study was prepared from coffee skin. The research was carried out from April 8 to July 19, 2019,This research was conducted in Pontianak West Kalimantan. The experiment is arranged  according to factorial randomize block design with two factors, i.e., dosage of ash (Factor A) and dosage of cow manure (Factor B). Factor A consists of three levels is, a1 (30 ton/ha equivalent to 15 kg/plot), a2 (40 ton/ha equivalent to 20 kg/plot), a3 (50 ton/ha equivalent to 25 kg/plot) and factor B also consists of b1 (10 ton/ha equivalent to 5 kg/plot), b2 (20 ton/ha equivalent to 10 kg/plot), b3 (30 kg/ha equivalent to 15 kg/plot). Each treatments is replicated 4 times, and each of this experimental unit has 8 sample crops. The results showed that the applicaros of 50 ton/ha of coffee husk ash and 30 ton/ha of beef cattle fertilizer was the best dose togrowth and yield of sweet corn on peat soil.  Keywords: cow manure, coffee husk ash, peat soil, sweet corn.